2017
DOI: 10.31729/jnma.3271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alcohol Consumption and Knowledge About Alcohol at Bhimtar, Sindhupalchowk

Abstract: Introduction: Alcohol causes several health problems, economic and social consequences across the world. Nepal is a multicultural and multi-ethnic country with an ambivalent regarding alcohol use according to social, religious and cultural values. Alcohol use is very common and easily available everywhere in Nepal. Objective of study is to find the prevalence of alcohol consumption and knowledge of alcohol among people at Bhimtar. Methods: A cross sectional study was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…Our study supports the results found by Osei-Bonsu et al (2017) suggesting that male consumes more alcohol than the female in Ghana and alcohol consumption was highest among youth, age in between 20-25 years. It also supports the results in Nepalese context conducted by Manandhar et al (2017) in Sindhupalchok district who found that male consume more alcohol than female.…”
Section: Socio-demographic Characteristic Of Respondentssupporting
confidence: 89%
See 1 more Smart Citation
“…Our study supports the results found by Osei-Bonsu et al (2017) suggesting that male consumes more alcohol than the female in Ghana and alcohol consumption was highest among youth, age in between 20-25 years. It also supports the results in Nepalese context conducted by Manandhar et al (2017) in Sindhupalchok district who found that male consume more alcohol than female.…”
Section: Socio-demographic Characteristic Of Respondentssupporting
confidence: 89%
“…In Nepalese context, the study conducted by Thapa et al (2016) found that 60 percent of the population have experienced alcohol where 38 percent are found to be using it regularly and 10 percent uses it daily and out of total reproductive age women in Nepal, 24.7 percent of them consume alcohol. Manandhar et al (2017) in Sindhupalchok district found that the knowledge on impact of alcohol consumption varied on education level and male consume more alcohol than female. Similarly, Thapa et al (2016) have suggested that the urban poor's alcohol consumption in Kathmandu valley has sharply grown in past decades in Nepal with one out of ten drinkers drink daily, a third of all current drinkers drink more than one type of alcohol and nearly 47.60 percent people drink during social gathering and nearly one fifth of the drinkers' drink at home.…”
Section: Introductionmentioning
confidence: 99%
“…These rates are two times more than the report of national average (Ever consumed alcohol: 26.5%, Current drinker: 22%, Drinker within past 30 days: 17.4%), but was lower than that of report from Bhaktapur by Maharjan PL and Magar KT (ever consumed alcohol: 67% and current drinking: 56%), and from report of Manandhar N et al (ever consumed alcohol: 73.8%, current drinker: 62.8%). 4,10,11 In contrast, the prevalence was bit lower in the study conducted in squatter of Kathmandu by Thapa P et al (39.8% current drinker), and in Western Nepal 35.6% (according to Adhikari TB et al). 12,13 This shows a marked variation in the prevalence of alcohol consumption between the regions within a country, which could be due to the variation in the environmental factors, ethnicity, socio-demographic and economic factors between place to place, different level of accessibility and availability of alcoholic products, methodological difference and nature of the sample like sampling population characteristics and timeline.…”
Section: Discussionmentioning
confidence: 88%
“…10 Manandhar N et al also reported that the majority of the drinker initiated drinking before legal age among the respondent of Bhimtar, Sindupalchowk. 11 This may be due to their study setting and sample population with a high majority of persons from ethnic groups where alcohol is used traditionally and have a cultural practice of early initiation of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is relatively different in other site of study. The study in East Java and Makasar, Indonesia found that most of the population have low level of behaviour state [9,10,11].…”
Section: Resultsmentioning
confidence: 99%